Bahasa Inggris - Rinaldo; A. Haris (Postgraduate, University of Mataram, 2025)
The North Sumatra Basin is one of the major sedimentary basins in Indonesia with significant hydrocarbon potential. However, exploration in this region faces challenges due to overpressure, which can increase operational risks such as blowouts. This study aims to analyze pore pressure and overpressure formation mechanisms in Well Al using the Eaton method and a crossplot approach between sonic and density data. The analysis results indicate that the top overpressure is identified at a depth of 8,500 ft in the Keutapang Formation and continues into the Baong, Bampo, and Parapat Formations. Wireline log evaluation indicates anomalies in the sonic, neutron, and density logs, which are consistent with disequilibrium compaction patterns. The Dutta crossplot results also confirm the dominance of smectite minerals without transformation into illite, reinforcing that the primary overpressure mechanism is loading due to disequilibrium compaction. Accurate pore pressure modeling is necessary to improve drilling safety and efficiency in this area.